Escaping Islamic Religious Noise: The Pros and Cons of the Use of Mosque Loudspeakers in Indonesia - Riyanto, Waryani Fajar (Ulumuna, 2024)
One of the controversial issues in religious practice in contemporary Indonesia is concerned with the noise raising from places of religious worship. This study aims to explain the pros and cons of Indonesia's state policy on the guidelines for using loudspeakers in Muslim places of worship (mosques and musallas). The primary data is obtained from state regulations (Indonesia Ministry of Religious Affairs) regarding guidelines for using loudspeakers. The secondary data is gathered from relevant literature sources. The current study employed content and thematic analyses in qualitative research. This study finds the concept of loudspeaker moderation as an alternative for resolving the pros and cons of the state policy regarding the regulation of the use of loudspeakers. Loudspeaker moderation integrates three pillars, namely the landmark (mosque), the soundmark (azan), and the ethicmark (guidelines for the use of loudspeaker), toward the soundworld. The study findings may have implications for factors that may provide a rational understanding of the policy on regulating loudspeakers in places of worship, especially in mosques and musallas throughout Indonesia.